Long-term outcomes of peroral endoscopic myotomy for achalasia: a systematic review and meta-analysis - Vespa, Edoardo; Pellegatta, Gaia; Chandrasekar, Viveksandeep T.; Spadaccini, Marco; Patel, Harsh; Maselli, Roberta; Galtieri, Piera A.; Carlani, Elisa; Sharma, Prateek; Hassan, Cesare; Repici, Alessandro (Endoscopy, 2022)
Background The long-term outcomes of esophageal peroral endoscopic myotomy (POEM) are still unknown.Methods We searched electronic databases (MEDLINE/PubMed, EMBASE, Scopus) for studies assessing outcomes after POEM for esophageal achalasia with a minimum median follow-up duration of 36 months. Pooled rates of clinical success and postoperative reflux were calculated and compared with the same values at 12/24/36 months when available. Subgroup analyses were performed to explore the interstudy heterogeneity.Results From 1528 initial records, 11 studies (2017–2021) were included. A total of 2342 patients (age 48.1 [SD 6.8] years; 50.1 % males) with a median follow-up of 48 months (interquartile range 45–60) were analyzed. The pooled clinical success rate was 87.3 % (95 %CI 83.6 %–91.0 %; I2 = 73.1 %). The symptomatic reflux pooled rate was 22.0 % (95 %CI 14.4 %–29.5 %; I2 = 92.7 %). Three cases of peptic strictures and one Barrett’s esophagus were reported. The pooled rate of severe adverse events was 1.5 % (95 %CI 0.5 %–2.5 %; I2 = 52.8 %).Conclusions Long-term clinical efficacy of POEM persisted in 87 % of patients with achalasia. Post-POEM symptomatic reflux remained stable over time. The risk for Barrett’s esophagus and peptic strictures appeared minimal.